[BP.10.04] NORMALIZATION OF SYMPATHETIC NERVE TRAFFIC IN THE LONG TERM FOLLOW-UP AFTER BAROREFLEX ACTIVATION THERAPY IN HEART FAILURE PATIENTS: FINAL STUDY REPORT. (September 2017) - Seravalle, G.; Gronda, E.; Costantino, G.; Alberti, L.; Baronio, B.; Staine, T.; Rizzo, S.; Vanoli, E.; Mancia, G.; Grassi, G.
Abstract : Objective: Baroreflex activation therapy (BAT) exerts in severe heart failure (HF) sympathoinhibitory effects concomitantly improving clinical variables and reducing hospitalization rate. The aim of this study was to determine long-term effects of BAT in HF patients. Design and method: Eleven HF patients aged 67 ± 9 years, mean ± SD in NYHA Class III HFrEF with left ventricular ejection fraction 40% and impaired functional capacity were enrolled in the study. Muscle sympathetic nerve activity (microneurography) and hospitalization rate together with standard clinical data were collected at 24 and 42 months following BAT activation. Microneurographic data were compared to those collected in an age-matched healthy control group. All assessments were made while on optimal active therapy. Results: Four patients died during the long-term follow-up (only 1 of cardiac nature). In the 7 surviving patients BAT maintained its beneficial effects over a long-term follow-up of 42.5 ± 3.5 months. MSNA values at baseline, 24 and 42 months follow-up were respectively: 466, 318 e 263 bursts/min and 6911, 4612 and 408 bursts/100 heart beats, becoming at the study end almost superimposable to the ones seen in healthy subjects. Blood pressure and heart rate did not change over the time. Left ventricular ejection fraction improved significantly from 31 ± 6% at baseline to 37 ± 9% at 42 month of BAT (P < 0.02). Hospitalization rate decreased substantially when measured as days/year/patients it decreased from 10.3 ± 7.8 pre-implant to 1.01 ± 1.3 at the 42 months follow up (P < 0.02). No side effects were reported in the long-term period. Conclusions: The present study provides evidence that BAT in CHF allows not only to improve hemodynamic and clinical profile but also to exert profound sympathoinhibitory effects allowing an almost complete normalization of sympathetic neural function.